Enhancing Students Speaking Ability Through Effortless English Video Technique - Prasetiyowati, Eni; Muhyidin, Moh. (Jurnal Pendidikan Bahasa Inggris Proficiency, 2026)
This research explores the use of the Effortless English Video Technique to enhance students’ speaking ability at Universitas Islam Negeri Syekh Wasil Kediri. Speaking is one of the essential skills in English learning, yet many students still face difficulties such as lack of confidence, limited vocabulary, poor pronunciation, and fear of making mistakes. The Effortless English Video Technique which is developed by A.J. Hoge provides an engaging way to help students speak fluently and naturally through repeated listening and speaking practices using authentic English videos. The study aims to describe the implementation of this technique and to investigate its potential in improving students’ speaking ability. The research employs a Classroom Action Research (CAR) design using McTaggart’s model, consisting of planning, acting, observing, and reflecting stages conducted in two cycles. The participants are first semester students of the English Department. Data are collected through observation, questionnaires, and speaking tests. The quantitative results showed a significant improvement: the mean score increased from 76,39(pre-test) to 83.71 (post-test, cycle 2), indicating a 9,6% increase in the class average. Crucially, the percentage of students achieving the Minimum Mastery Criterion (KKM) (a score of 75) substantially increased from 46% in the pre-test to 89% in the post-test. Questionnaire results indicated a high positive perception from students, especially regarding increased motivation and public speaking confidence. Therefore, the Effortless English Video Technique is proven to be an effective and engaging method for enhancing students' speaking ability.